Open-Minded Midwifes, Literate Butchers, and Greedy Hooligans—The Independent Contributions of Stereotype Valence and Consistency on Evaluative Judgments - Schubert, Lisa; Körner, Anita; Lindau, Berit; Strack, Fritz; Topolinski, Sascha (Frontiers in Psychology, 2017)
Do people evaluate an open-minded midwife less positively than a caring midwife? Both open-minded and caring are generally seen as positive attributes. However, consistency varies—the attribute caring is consistent with the midwife stereotype while open-minded is not. In general, both stimulus valence and consistency can influence evaluations. Six experiments investigated the respective influence of valence and consistency on evaluative judgments in the domain of stereotyping. In an impression formation paradigm, valence and consistency of stereotypic information about target persons were manipulated orthogonally and spontaneous evaluations of these target persons were measured. Valence reliably influenced evaluations. However, for strongly valenced stereotypes, no effect of consistency was observed. Parameters possibly preventing the occurrence of consistency effects were ruled out, specifically, valence of inconsistent attributes, processing priority of category information, and impression formation instructions. However, consistency had subtle effects on evaluative judgments if the information about a target person was not strongly valenced and experimental conditions were optimal. Concluding, in principle, both stereotype valence and consistency can play a role in evaluative judgments of stereotypic target persons. However, the more subtle influence of consistency does not seem to substantially influence evaluations of stereotyped target persons. Implications for fluency research and stereotype disconfirmation are discussed.